Decreases in Antimicrobial Use Associated With Multihospital Implementation of Electronic Antimicrobial Stewardship Tools - Graber, Christopher J (Clin Infect Dis, 2020)
BACKGROUND: Antimicrobial stewards may benefit from comparative data to inform interventions that promote optimal inpatient antimicrobial use. METHODS: Antimicrobial stewards from 8 geographically dispersed Veterans Affairs (VA) inpatient facilities participated in the development of antimicrobial use visualization tools that allowed for comparison to facilities of similar complexity. The visualization tools consisted of an interactive web-based antimicrobial dashboard and, later, a standardized antimicrobial usage report updated at user-selected intervals. Stewards participated in monthly learning collaboratives. The percent change in average monthly antimicrobial use (all antimicrobial agents, anti-methicillin-resistant Staphylococcus aureus [anti-MRSA] agents, and antipseudomonal agents) was analyzed using a pre–post (January 2014–January 2016 vs July 2016–January 2018) design with segmented regression and external comparison with uninvolved control facilities (n = 118). RESULTS: Intervention sites demonstrated a 2.1% decrease (95% confidence interval [CI], −5.7% to 1.6%) in total antimicrobial use pre–post intervention vs a 2.5% increase (95% CI, 0.8% to 4.1%) in nonintervention sites (absolute difference, 4.6%; P = .025). Anti-MRSA antimicrobial use decreased 11.3% (95% CI, −16.0% to −6.3%) at intervention sites vs a 6.6% decrease (95% CI, −9.1% to −3.9%) at nonintervention sites (absolute difference, 4.7%; P = .092). Antipseudomonal antimicrobial use decreased 3.4% (95% CI, −8.2% to 1.7%) at intervention sites vs a 3.6% increase (95% CI, 0.8% to 6.5%) at nonintervention sites (absolute difference, 7.0%; P = .018). CONCLUSIONS: Comparative data visualization tool use by stewards at 8 VA facilities was associated with significant reductions in overall antimicrobial and antipseudomonal use relative to uninvolved facilities.